2009
DOI: 10.1007/s00066-009-1983-y
|View full text |Cite
|
Sign up to set email alerts
|

Local Relapse after Breast-Conserving Surgery and Radiotherapy

Abstract: This analysis again shows that the survival parameters are worsening after local relapse, especially in case of early occurrence. In breast cancer treatment, therefore, the goal remains to avoid local failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
4
0
2
Order By: Relevance
“…According to current guidelines, chest wall irradiation is indicated in patients with T3 or T4 tumors, node-positive disease, or in patients with marginal or incomplete resection [12,20]. The benefits of chest wall irradiation have been illustrated in many prospective trials and several metaanalyses [8,19,25,26]. It has, thus, been demonstrated that adjuvant radiotherapy reduces the risk of local relapse by approximately two-thirds ultimately improving long-term survival of the patients [7,19,23,2].…”
Section: Introductionmentioning
confidence: 99%
“…According to current guidelines, chest wall irradiation is indicated in patients with T3 or T4 tumors, node-positive disease, or in patients with marginal or incomplete resection [12,20]. The benefits of chest wall irradiation have been illustrated in many prospective trials and several metaanalyses [8,19,25,26]. It has, thus, been demonstrated that adjuvant radiotherapy reduces the risk of local relapse by approximately two-thirds ultimately improving long-term survival of the patients [7,19,23,2].…”
Section: Introductionmentioning
confidence: 99%
“…Odsetek ten był większy, niż obserwowany odsetek nawrotów miejscowych po mastektomii (2,3%) [2]. W dużym badaniu pochodzącym z lat 1984-1997 (352 kobiety poddane szerokiemu wycięcia guza i uzupełniającej radioterapii; mediana okresu obserwacji 100 miesięcy) odsetek IBRT wynosił 5,4% [7]. Z kolei w badaniu opublikowanym w roku 2012 odsetek IBTR (grupa > 12 000 kobiet poddanych leczeniu oszczędzającemu w latach 1997-2004, okres obserwacji > 5 lat) był istotnie mniejszy niż w poprzednich dekadach i sięgał 2,5% [8].…”
Section: Ryzyko Wystąpienia Ibrtunclassified
“…W badaniu nieco bardziej współ-czesnym, obejmującym lata 90. XX wieku (okres obserwacji wynosił 10 lat), łącznie u 17,1% chorych zamiast mastektomii prostej z powodu IBRT po leczeniu oszczędzającym pierś podjęto próbę kolejnego miejscowego wycięcia IBRT [7].…”
Section: Przesłanki Do Zmiany Standarduunclassified
“…Yates et al [50] found a significantly lower 10-year survival in case of supraclavicular failure, which is why PCLNI should be considered in this subset of patients. According to Hammer et al [22], there is a significant association between time to relapse and a poorer prognosis; thus, the mayor goal should be the avoidance of local recurrences. On the other hand, the selection of a special subgroup of patients with 1-3 pN+ in whom the effect of RT outbalances the possible late side effects is of great importance.…”
Section: Periclavicular Irradiationmentioning
confidence: 99%